The Evolution of Photospheric Magnetic Fields at the Footpoints of Reconnected Structures in the Solar Atmosphere - Tao Ding; Jun Zhang; Yue Fang; Junchao Hong; Yi Bi; Yongyuan Xiang (The Astrophysical Journal, 2024)
Magnetic reconnection is believed to play an important role in the release and conversion of energy among magnetized plasma systems. So far, we have been unable to understand under what conditions magnetic reconnection can take place. Based on observations from the New Vacuum Solar Telescope and the Solar Dynamics Observatory (SDO), we study 16 magnetic reconnection events, and each event has a clear X-type configuration consisting of two sets of atmospheric structures. We focus on 38 footpoints that are relevant to these structures and can be clearly determined. By using SDO/Helioseismic and Magnetic Imager line-of-sight magnetograms, we track the field evolution of these footpoints. Prior to the occurrence of magnetic reconnection, the associated fields at the footpoints underwent convergence and shear motions, and thus became enhanced and complex. During the converging period, the rates of increase of the mean magnetic flux densities (MFDs) at these footpoints are 0.03–0.25 hr ^−1 . While the unsigned mean MFDs are 70–300 G, magnetic reconnection in the solar atmosphere takes place. Subsequently, the photospheric fields of these footpoints diffuse and weaken, with rates of decrease of the MFDs from 0.03 to 0.18 hr ^−1 . These results suggest that, due to the photospheric dynamical evolution at the footpoints, the footpoint MFDs increase from a small value to a large one, and the corresponding atmospheric magnetic fields become complicated and nonpotential; then reconnection happens and it releases the accumulated magnetic field energy. Our study supports the conjecture that magnetic reconnection releases free magnetic energy stored in the nonpotential fields.